2015
DOI: 10.1111/camh.12137
|View full text |Cite
|
Sign up to set email alerts
|

Service users as the key to service change? The development of an innovative intervention for excluded young people

Abstract: Background Excluded young people, especially those affected by street gangs, often have complex unmet needs and high levels of health and social inequalities. This paper outlines the development of Music & Change, an innovative and comprehensive intervention accessible to young people, which aimed to holistically meet the mental health and other needs of its participants and ultimately to reduce offending rates. Its central principle was coproduction and partnership with its potential users. Method The setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Most of it is yourself but the environment was helpful to facilitate that growth and the fact you can drop in after a few months. (Jack) Similarly, Zlotowitz et al (3)found that in order to engage excluded young people, long-term, consistent relationships with practitioners who were caring, non-judgemental and trustworthy was essential. Participants' experiences of clubhouse staff certainly met this threshold, helping young adults to feel needed as valuable members of society.…”
Section: Social Inclusion -How My Life Has Changed [A]mentioning
confidence: 99%
“…Most of it is yourself but the environment was helpful to facilitate that growth and the fact you can drop in after a few months. (Jack) Similarly, Zlotowitz et al (3)found that in order to engage excluded young people, long-term, consistent relationships with practitioners who were caring, non-judgemental and trustworthy was essential. Participants' experiences of clubhouse staff certainly met this threshold, helping young adults to feel needed as valuable members of society.…”
Section: Social Inclusion -How My Life Has Changed [A]mentioning
confidence: 99%
“…The Integrate model is an approach to mental health service development and design for excluded young people and is described in detail elsewhere. 19 The model aims to reduce offending, improve young people’s mental health, support access to services and employment, and create change at wider levels. The target group for this particular project were people aged 16–25 who were involved in serious offending behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…The pilot was led by the charity MAC-UK in partnership with a NHS trust and the local authority. The Integrate model is an approach to mental health service development and design for excluded young people and is described in detail elsewhere 19. The model aims to reduce offending, improve young people’s mental health, support access to services and employment, and create change at wider levels.…”
Section: Introductionmentioning
confidence: 99%
“…The insider perspective was offered by some participants who were part of ameliorative policy development, at the heart of government systems such as the United Kingdom National Health Service and public health departments (Michie, 2008; Richardson, 2015). Other participants offered an outsider perspective on transformative policy change, attempting to challenge the status quo and power structures, developing campaigns, and giving a voice to marginalized groups affected by policy (Allen, 2013; Burton, 2013; Holland, 2006; Nelson, 2013; Zlotowitz, Barker, Moloney, & Howard, 2016). Maton (2016) refers to these as varying “vantage points” from which psychologists choose to influence policy, working with different stakeholder groups to achieve the same outcome.…”
Section: Discussionmentioning
confidence: 99%